The Role of Information System for Risk Management in Hospital: A Narrative Review - Sutejo Sutejo; Agung Budi Prasetijo; Farid Agushybana (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2021)
The development and progress of information technology is growing rapidly, including information technology in hospital services. Hospitals are labor-intensive, technology-intensive, and risk-taking institutions that require proactive strategies and solutions in risk management. Integrated Risk Management Information System (IRMIS) is defined as an organized and integrated strategy for hospital risk control which consists of identification, assessment, implementation of strategies to reduce or eliminate risks, and monitoring and reviewing risks in hospitals. Management of patient care directly is often associated with risk management. The concept of risk management was developed from clinical and non-clinical services by considering patient safety and security. In this scenario, risk management should be viewed as a proactive activity in maintaining and maintaining the quality of hospital services and the confidentiality of patient data and information and managed in an integrated manner with the hospital management information system (SIMRS) and/or other applications in the hospital as well as business process integration. hospital. This study uses a narrative review approach, with many articles on the same issue. Articles were taken from the Scopus, Science Direct, ProQuest, SpringerLink, Google Scholar, Nature, JSTOR, and Emerald Insight databases with a total of 29 articles used. The purpose of this study was to determine whether the integrated risk management developed in the hospital has a significant influence on decision making with strategic support systems such as human resource development, program selection, marketing, and facility growth by considering clinical and non-clinical risks in the hospital.  Abstrak: Perkembangan dan kemajuan teknologi informasi semakin pesat, termasuk teknologi informasi dalam pelayanan di rumah sakit. Rumah sakit sebagai institusi yang padat karya, padat teknologi, sekaligus padat risiko yang memerlukan strategi dan solusi proaktif dalam pengelolaan risiko. Sistem Informasi Manajemen Risiko Terintegrasi (SMART) didefinisikan sebagai strategi terorganisir dan terintegrasi untuk pengendalian risiko rumah sakit yang terdiri dari identifikasi, penilaian, penerapan strategi untuk mengurangi atau menghilangkan risiko, dan pemantauan dan reviu risiko di rumah sakit. Manajemen pelayanan pasien secara langsung sering dikaitkan dengan manajemen risiko. Konsep manajemen risiko dikembangkan dari pelayanan klinis dan non klinis dengan mempertimbangan keamanan dan keselamatan pasien. Dalam skenario ini, manajemen risiko harus dipandang sebagai aktivitas proaktif dalam menjaga dan mempertahankan kualitas pelayanan rumah sakit dan kerahasiaan data dan informasi pasien serta dikelola secara terintegrasi dengan sistem informasi manajemen rumah sakit (SIMRS) dan/ atau aplikasi lain di rumah sakit serta integrasi proses bisnis rumah sakit. Penelitian ini menggunakan pendekatan naratif review, dengan banyak artikel tentang masalah yang sama. Artikel diambil dari database Scopus, Science Direct, ProQuest, SpringerLink, Google Scholar, Nature, JSTOR, dan Emerald Insight dengan total 29 artikel yang digunakan. Tujuan penelitian ini adalah untuk mengetahui apakah manajemen risiko terintegrasi yang dikembangkan di rumah sakit memiliki pengaruh signifikan dalam pengambilan keputusan dengan sistem pendukung strategis seperti pengembangan sumber daya manusia, pemilihan program, pemasaran, dan pertumbuhan fasilitas dengan mempertimbangkan risiko klinis dan non klinis di rumah sakit.